Dietary polyphenols and human health: sources, biological activities, nutritional and immunological aspects, and bioavailability– a comprehensive review - Saad, Ahmed M.; Mohammed, Dina Mostafa; Alkafaas, Samar Sami; Ghosh, Soumya; Negm, Shaimaa H.; Salem, Heba M.; Fahmy, Mohamed A.; Semary, Hatem E.; Ibrahim, Essam H.; AbuQamar, Synan F.; El-Tarabily, Khaled A.; El-Saadony, Mohamed T. (Frontiers in Immunology, 2025)
Dietary polyphenols, particularly flavonoids, have been extensively recognized for their role as a source of bioactive molecules that contribute to the prevention of various diseases, including cancer. This review aims to provide a comprehensive overview of dietary polyphenols by examining their sources, classification, mechanisms of action, and biological effects, with a particular emphasis on their nutritional and immunological roles. It also highlights the need for ongoing research into preventive strategies and the development of improved therapeutic options. Despite their broad spectrum of antioxidant, anti-inflammatory, neuroprotective, antimicrobial, anti-diabetic, and anti-cancer activities, the therapeutic application of polyphenols is significantly hindered by their inherently poor bioavailability. This limitation poses a substantial challenge, as it prevents polyphenols from achieving the systemic concentration necessary to elicit a therapeutic effect. This review critically evaluates current strategies, including nano- and liposomal-based delivery systems. Liposomal systems play a crucial role in enhancing the bioavailability of polyphenols by encapsulating these compounds in lipid bilayers. This encapsulation improves the solubility and stability of polyphenols, protects them from environmental degradation and rapid metabolism, and facilitates their controlled release and absorption in the body. Liposomes enable polyphenols to better traverse biological membranes and protect them from unfavorable conditions in the gastrointestinal tract, resulting in greater systemic availability and improved therapeutic efficacy compared to non-encapsulated forms. The current review also explores the modulatory impact of polyphenols on the immune system, their influence on gut microbiota, and their implications across various life stages, from infancy to aging, as well as in athletic performance and dermatological health. Future directions are proposed to optimize their clinical utility, including standardized dosing, improved delivery technologies, and targeted nutritional interventions. Ultimately, integrating polyphenols into daily dietary practices may offer promising avenues for enhancing immune resilience and preventing chronic diseases.